Designing a combined coulter for exemplary sowing of cereals (Revista de Investigaciones Universidad del Quindío, 2022)
Agrochemical science and progressive practice have developed requirements for sowing crops and, in particular, grain. They will place the seeds in a moisture-proof layer to a predetermined depth on the prepared bed. This study aims to investigate designing a combined colter for exemplary sowing of cereals. To that end, to avoid these shortcomings in the technology of grain crops sowing, a technical solution in the form of sowing sections is proposed. Based on the results, the principal amount of fertilizers should be applied locally, in the soil near the seeds, below the sowing level by 3...7 cm. The soil above the seeds should be compacted with a density of 1.15...1.25 g/cm3. Analysis of the designs of grain seeders and the proposed technical solutions for the combined sowing showed that there are no devices that meet all the requirements. It provides loosening of the soil in the area of fertilizer and seed placement, sows fertilizer to the bottom of the furrow, covers it with soil, forms a compacted bed under the seeds, sows the seeds on the compacted bed, covers them with soil and compacts it over the seeds.
Keywords: seeding; seeds; fertilizers; combined; combination